2003
DOI: 10.1093/humrep/deg289
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in women with PCOS and in controls matched by age and weight

Abstract: When differences in age and weight between PCOS patients and controls are negligible, PCOS is not associated with a higher risk of pregnancy complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
92
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 16 publications
11
92
5
1
Order By: Relevance
“…Most studies reporting an association between hypertension or pre-eclampsia and pregnancy in PCOS show mixed results. 28 In our study, none of the PCOS women developed gestational hypertension with or without metformin treatment. The study by Mikola showed that PCOS was not a significant predictor of preeclampsia compared with control pregnancies.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Most studies reporting an association between hypertension or pre-eclampsia and pregnancy in PCOS show mixed results. 28 In our study, none of the PCOS women developed gestational hypertension with or without metformin treatment. The study by Mikola showed that PCOS was not a significant predictor of preeclampsia compared with control pregnancies.…”
Section: Discussionmentioning
confidence: 45%
“…The link between PCOS and gestational diabetes was initially suggested by several retrospective series. [26][27][28] Women with PCOS who are insulin resistant are at high risk for the development of diabetes in pregnancy. In a large population based study, GDM has been reported to affect up to 18% of patients diagnosed with PCOS with an odds ratio of 2.4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Rotterdam consensus [3], PCOS is defined as the presence of two of the following criteria: hyperandrogenism, ovulatory dysfunction, and polycystic ovaries on ultrasound (12 or more follicles, 2-9 mm in diameter, and/ or increased ovarian volume >10 ml); disorders that mimic the clinical features of PCOS are excluded [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These alterations can lead to glucose metabolism disorders and increased risk of developing gestational diabetes mellitus (GDM). Furthermore, pregnancy itself induces insulin resistance [1,2,4,5].…”
Section: Introductionmentioning
confidence: 99%